Characterization of residual stresses in zirconia veneered bilayers assessed via sharp and blunt indentation - Wendler, Michael; Belli, Renan; Petschelt, Anselm; Lohbauer, Ulrich (Dental Materials, 2015)
The present study evaluated the effect of the coefficient of thermal expansion (CTE) mismatch and the cooling protocol on the distribution of residual stresses and crack propagation in veneered zirconia bilayers.Ceramic discs with two different CTEs (Vita VM9 and Lava Ceram) were fired onto zirconia plates and cooled following a slow (0.5°C/s) or a fast (45°C/s) cooling protocol. The residual stress distribution throughout the veneer thickness was assessed by means of depth-wise Vickers indentation after sequentially sectioning the bilayers parallel compared to normal to the interface. A mathematical solution for the residual stress distribution was used as reference. Additionally, Hertzian cone crack propagation in the veneers was induced by cyclic contact loading and measured at different number of cycles to estimate the crack growth rate.The higher CTE mismatch of the VM9 group generated an important stress gradient with high compressive residual stresses near the interface, hindering the crack propagation. The low CTE mismatch group (Lava Ceram) developed only a slight stress gradient and higher cone crack growth rates. No differences were observed between the two cooling protocols applied regarding stress magnitude and crack propagation behavior.The CTE mismatch has a predominant role in the generation of residual stress gradients within the veneer, which directly influences contact-induced crack propagation. Based on the results, the cooling protocol had no significant effect on the residual stress distribution in zirconia-veneer bilayers.
EVALuna2:24676